Roseovarius azorensis sp nov., isolated from seawater at espalamaca, azores - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Thi-Nhan Khieu; Chu Ky Son; Li, Wen-Jun; Colaco, Ana (Antonie van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A Gram-negative, motile, non-spore forming, rod shaped aerobic bacterium, designated strain SSW084(T), was isolated from a surface seawater sample collected at Espalamaca (38A degrees 33'N; 28A degrees 39'W), Azores. Growth was found to occur from 15 to 40 A degrees C (optimum 30 A degrees C), at pH 7.0-9.0 (optimum pH 7.0) and with 25-100 % seawater or 0.5-7.0 % NaCl in the presence of Mg2+ and Ca2+; no growth was found with NaCl alone. Colonies on seawater nutrient agar were observed to be punctiform, white, convex, circular, smooth, and translucent. Strain SSW084(T) did not grow on Zobell marine agar and tryptic soy agar even when seawater supplemented. The major respiratory quinone was found to be Q-10 and the G + C content was determined to be 61.9 mol%. Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain SSW084(T) belongs to the genus Roseovarius and that its closest neighbours are Roseovarius tolerans EL-172(T), Roseovarius mucosus DFL-24(T) and Roseovarius lutimaris 112(T) with 95.7, 95.4 and 95.3 % sequence similarity respectively. The remaining species of Roseovarius showed < 95 % similarity. The polar lipids of strain SSW084(T) were determined to be phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, an unidentified lipid and one unidentified aminolipid. The major fatty acids identified were identified as C-18:1 omega 7c (52.5 %) and C-16:0 (13.8 %). On the basis of phenotypic, molecular and chemotaxonomic characteristics, strain SSW084(T) is considered to represent a novel species of the genus Roseovarius, for which Roseovarius azorensis sp. nov is proposed. The type strain is SSW084(T) (=KCTC 32421(T) = MTCC 11812(T)).
Keywords: Espalamaca; Polyphasic taxonomy; Roseovarius azorensis sp nov; Seawater